ETHNOCENTRIC ATTITUDES AND BUYING DECISIONS OF POLES AND HUNGARIANS – THE ESSENCE AND MEASUREMENT WITH THE USE OF CETSCALE ANALYSIS - Andrzej Szromnik; Elżbieta Wolanin-Jarosz (Polityki Europejskie, Finanse i Marketing)
In the following article the results of empirical researches have been discussed. Their aim was to define the consumer ethnocentrism level of the inhabitants of Poland and Hungary. The main source material was acquired thanks to direct interviews, conducted in two towns: Rzeszów (Poland) and Debrecen (Hungary), in a chosen group of 800 respondents (400 people in each town). The international CETSCALE questionnaire has been used as a measuring instrument. The analyses presented, clearly indicate that, Polish as well as Hungarian consumers show ethnocentric tendencies. However significantly bigger CET scale values have been obtained in Hungarian community. It has also been noted that demographic factors have meaningful influence on the ethnocentric level of the both groups researched.